1982
DOI: 10.1002/j.1537-2197.1982.tb13242.x
|View full text |Cite
|
Sign up to set email alerts
|

Stipe Anatomy, Water Potentials, and Xylem Conductances in Seven Species of Ferns (Filicopsida)

Abstract: Anatomy and water relations were studied for the desert fern Notholaena parryi, as well as six other ferns representing three different orders which occupied xeric as well as mesic habitats. Tracheid number and diameter, and total xylem cross sectional area increased during leaf development for N. parryi; the whole plant conductance (volume flow of water through a stipe divided by the rhizome‐to‐leaf water potential drop) increased but tended to level off as the leaves matured. The reported occurrences of very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…This is likely explained by the well‐ known relationship between topography and soil moisture (Huggett and Cheeseman 2002, Petter et al 2015), which can influence plant communities (Dearborn and Danby 2017, Muscarella et al 2020). Further, resprouting ferns are typically shade‐tolerant and occupy mesic environments with high soil moisture due to their poor control of water conduction and loss (Woodhouse and Nobel 1982, Hunt et al 2002, Page 2002). Therefore, these species can be sensitive to water stress (Hunt et al 2002, Volkova et al 2010, Riaño and Briones 2013) and the harsh solar radiation associated with north‐facing slopes (Petter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely explained by the well‐ known relationship between topography and soil moisture (Huggett and Cheeseman 2002, Petter et al 2015), which can influence plant communities (Dearborn and Danby 2017, Muscarella et al 2020). Further, resprouting ferns are typically shade‐tolerant and occupy mesic environments with high soil moisture due to their poor control of water conduction and loss (Woodhouse and Nobel 1982, Hunt et al 2002, Page 2002). Therefore, these species can be sensitive to water stress (Hunt et al 2002, Volkova et al 2010, Riaño and Briones 2013) and the harsh solar radiation associated with north‐facing slopes (Petter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, passive stomatal control has been reported several times in ferns (Brodribb & McAdam, 2011; Cardoso, Randall, & McAdam, 2019; McAdam & Brodribb, 2012; Ruszala et al, 2011), suggesting that they possess a diminished capacity to optimize water‐use efficiency (Brodribb, McAdam, Jordan, & Feild, 2009). A suite of studies also reveals how anatomical traits directly influence fern water relations and gas exchange in a manner that is functionally different from seed plants (Baer, Wheeler, & Pittermann, 2016; Brodersen, Roark, & Pittermann, 2012; Brodribb, Holbrook, Zwieniecki, & Palma, 2005; Pittermann, Limm, Rico, & Christman, 2011; Woodhouse & Nobel, 1982; Zhang, Chen, Li, & Cao, 2009). Taken together, the weight of the evidence suggests that fern ecophysiology is inherently constrained, leaving means by which a third of all tropical fern species adapted and diversified into canopy habitats an open question (Schuettpelz & Pryer, 2009; Zotz, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the hydraulic conductivity of fern stipes range from the low end of angiosperms to several orders of magnitude lower (Woodhouse & Nobel, 1982; Veres, 1990), resulting in large pressure gradients during transpiration (Nobel, 1978). These observations have been used to explain the low photosynthetic and growth rates typically exhibited by pteridophytes, suggesting inefficient delivery of water to the mesophyll as a limiting factor to photosynthesis (Woodhouse & Nobel, 1982). By contrast, a recent study demonstrated high photosynthetic rates (implying high hydraulic conductivity) and low stomatal sensitivity to changes in vapour pressure deficit (VPD) (implying the opposite) in two vessel bearing fern species (Franks & Farquhar, 1999).…”
Section: Introductionmentioning
confidence: 99%